Waste to Energy Menuju Kemandirian Energi dan Zero Waste di Indonesia - Savitri, Indira; Sulendra, Ketut (Jurnal Teknologi Berkelanjutan, 2025)
Utilization of waste as an energy source for Waste-to-Energy Power Plants is an implementation of Waste to Energy (WtE). This research begins by calculating the potential waste generation in each province in Indonesia based on data from the National Waste Management Information System in 2024 and the projected waste generation in 2025. The calculation is based on the assumption that every 1000 tons/day of waste has the potential to be converted into energy of 20 MW. The results of the calculation of electrical power from the potential waste generation in 2025 of around 60-65 million tons obtained electrical power of around 3,655 MW or 3.655 GW. Based on the volume of waste generation in each province, the potential for electrical power is divided into 5 (five) categories, namely the Very Large category for West Java and East Java with an electrical power of 350-500 MW, the Large category with a power of 160-350 MW in DKI Jakarta and Central Java, the Medium category in Banten and South Sulawesi with an electrical power of 60-180 MW and the Small category with a potential electrical power of 20-60 MW in Aceh, North Sumatra, Riau, West Sumatra, South Sumatra, Lampung, DI Yogyakarta, Bali, NTB, NTT, West Kalimantan, Central Kalimantan, South Kalimantan, East Kalimantan and North Sulawesi. The remaining 17 of the 38 provinces are in the Very Small category with an electrical power of only 0-20 MW. The number of PLTSa that has the potential to be built is around 34 units, namely 5 units in West Java, 4 units in East Java, 3 units in DKI Jakarta and Central Java, 2 units in Banten and South Sulawesi and 1 unit each in 15 provinces with a small category power.